The Prevalence of Cardiovascular Disease Risk Factors: An Age-matched Analysis from FiLWHEL (2014–2016), NNS (2008), KNHANES (2013–2015) and NHANES (2013–2016) Data (P18-088-19). (13th June 2019) - Provido, Sherlyn Mae; Abris, Grace; Kim, An Na; Hong, Sangmo; Yu, Sung Hoon; Lee, Chang Beom; Lee, Jung Eun
Abstract: Objectives: Cardiovascular disease (CVD) is accountable for major cause of deaths among women worldwide. We aimed to assess the prevalence of CVD risk factors among Filipino women in Korea, Filipino women in the Philippines, Korean women in Korea and US women in the US. Methods: We randomly selected a sample of 504 women from each study using a 1:1 age-matching analysis. Age range from 20–57 years old. We analyzed anthropometry, blood pressure and biomarkers data from the Filipino Women's Health and Diet Study (FiLWHEL), the Philippine National Nutrition Survey (NNS), Korean National Health and Nutrition Examination Survey (KNHANES) and the US National Health and Nutrition Examination Survey (NHANES). We used the American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) criteria to categorize blood lipids. We assessed the prevalence of CVD risk factors using proportions, means and standard deviations. Results: We found that high BMI (≥25 kg/m²) and high waist circumference (WC: ≥85 cm) were prevalent in NHANES (65.6%, mean BMI = 29.48 ± 8.18 and 70.8%, mean WC = 96.16 ± 18.19, respectively) than in FiLWHEL (30.9%, 26.4% respectively), NNS (29.0%, 23.9% respectively) and KNHANES (19.8%, 12.0% respectively), p -value = <.0001. NHANES also exhibited higher prevalence for high cholesterol (≥200 mg/dL), high triglyceride (≥150 mg/dL) and high glucose (≥110 mg/dL) with 32.3%, 25.4% and 10.8% respectively. However, compared with NHANES (28.3%) and KNHANES (21.6%), NNS and FiLWHEL had higher prevalence of pre-hypertension and hypertension combined (47.6% and 43.8%, respectively), p -value = < .0001. Also, high prevalence of low HDL-c (<50 mg/dL) was striking in NNS (39.84 ± 5.75) than in FiLWHEL (58.19 ± 14.06), NHANES (57.44 ± 16.76) and KNHANES (56.97 ± 11.35). Conclusions: Our study suggest that the prevalence of risk factors for cardiovascular disease were different across Filipino women in Korea and in the Philippines, Korean women and US women. Funding Sources: Handok Pharmaceutical Co., Ltd.